Robust trajectory maneuvering of VTOL aircraft using higher-order sliding mode control (HOSMC) - Dagal, Idriss; Erol, Bilal (NATURE PORTFOLIO, 2025)
Vertical Takeoff and Landing (VTOL) aircraft present significant control challenges due to their nonlinear, strongly coupled dynamics and sensitivity to disturbances, particularly during hover-forward flight transitions. This study focuses on developing a Higher-Order Sliding Mode Control (HOSMC) strategy, based on the Super-Twisting algorithm, to enhance trajectory tracking accuracy and robustness for small-scale VTOL platforms. The proposed method was designed with tailored sliding variables and refined gain tuning, and its performance was validated through extensive simulations under realistic urban flight conditions, including Dryden-model turbulence, thrust perturbations, and multi-phase trajectories. Results show that HOSMC achieved superior tracking performance, with a maximum error of 0.038 m and an RMS error of 0.017 m, representing a 61% improvement in RMS error over SMC and a 50% reduction in maximum error compared to ASMC, while also delivering smoother control inputs, a thrust-to-weight ratio of 0.17, and energy consumption as low as 0.1866 kWh/h. These findings confirm that HOSMC not only suppresses chattering but also improves energy efficiency by up to 20% compared to PID, underscoring its potential as a robust and efficient control solution for autonomous VTOL operations in urban air mobility (UAM) applications.
Keywords: Higher-Order sliding mode control (HOSMC); Vertical takeoff and landing (VTOL); Trajectory tracking; Robust control; Disturbance rejection; TRACKING CONTROL; Science & Technology - Other Topics